Essence and Application of Modular Learning Technology - M., Abdumonnonov (European Journal of Life Safety and Stability (2660-9630), 2021)
This article analyzes one of the most pressing issues in the education system of the country, the analysis of the achievements of modular learning technologies in recent years, the requirements for the practical application of modular learning technologies and the rules, the purpose and essence of modular learning technology, and the work to be done to develop the modules.